(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Aim This study is aimed to assess the prescription pattern in DM patients with co morbid condition, because prescription pattern could lead to worsening of disease and increased risk of complications. The specific and general aspects of diabetic patients including the available dosage forms, to patients, drug interactions observed and common co morbities seen in diabetic patients, all add to difficulties facing by the practitioner who treats them. Due to the above reasons the study was designed to help minimize the prescription errors, render safe dosage regimen, by carefully monitoring the patientsglyceminc control and other responses towards therapy, finally improving the quality of life. Methodology This is a prospective observational study conducted over a period of six months using questionnaires as a tool. The study was conducted at Nephrology ward of AWARE GLOBAL HOSPITAL LB. NAGAR. Patients who admitted to the general ward of the hospital during a six-month period from October 2016 to March 2017 are enrolled. Results Based on inclusion and exclusion criteria, 98 patients were selected from the inpatient department over a period of 6 months for the present study. Among 98 patients The gender distribution found in the following study was males (64%) and females (36%), the age distribution was found to be 25-35 yrs (4%),35-45yrs (12%),45-55 yrs (24%), 55-65yrs (35%), 65-75 yrs (17%) ,75-85 yrs (8%). Of the total 98 cases enrolled the co morbid conditions found were Hypertension (76%), hypothyroidism (16%) and chronic kidney disease (15%). A total of 464 drugs were prescribed during the study period. 102 (22%) antidiabetics, 72(15.5%) antihypertensives, 59(12.72%) multivitamins, 46 (9.9%) antiplatelets, 20(4.31%) statins and 165(35.5%) miscellaneous drugs were prescribed. Conclusion The final report drawn from a total of 98 cases with the primary condition “DIABETES MELLITUS TYPE -II” the major co-morbid condition found was HYPETENSION (76 cases) in the study population. The standard therapy which showed good control for the condition Diabetes + Hypertension given was: • Ca+2 channel blockers (22.45% usage) eg. Amlodipine • β-Blockers (15.31%) eg. Metoprolol • Biguanides (43%) eg. Metformin • Human Mixtard Insulin (25%)